Ultrasonic motion detector / Mohd Lutfi Md Radzi and Nor Azura Samsudin - Md Radzi, Mohd Lutfi; Samsudin, Nor Azura (2005)
Ultrasonic motion detector is a simple circuit, which is used to detect the movement object example, human. When a moving object passes through the transducer than have the LED will light on for a few second and the same time the sound of doorbell on. This project is suitable used for every house because this gives some advantages for the both sides. As for the person, he will know automatically if there is stranger around the house. This circuit also safe to use because it used low voltage. It also is inexpensive because it just used simple electronic devices. The motion is detected by 40 kHz ultrasonic transmitting transducer in the transmitter section which also consists of 40 kHz crystal oscillator and 4069 hex inverter IC. 40 kHz receiving transducer in the receiver section then detect any reflect sound produce by transmitting. This section is also consists of TL 084 quad operational amplifier, which is used to amplify the signal, and turns ON the transistor Q1 and light this LED.